The impact of the principle of complementarity in defining the concept of international crime - Talaat Jiad Ljy Al-Hadidi (الرافدین للحقوق, 2009)
The international judicial system complains of weakness, not only at the structural level but also at the functional level. "The absence of hierarchy and organic unity among international tribunals has greatly contributed to the further weakness of this system. As an international attempt to strengthen the international judiciary, the International Criminal Court was established to emphasize the functional unity, especially in the criminal field between the national and international courts. The incorporation of its statute (the principle of integration) was a reference to the birth of the beginning of interdependence between these two systems.